Dynamic of Composition and Diversity of Gut Microbiota in Triatoma rubrofasciata in Different Developmental Stages and Environmental Conditions - Hu, Yue; Xie, Hanguo; Gao, Minzhao; Huang, Ping; Zhou, Hongli; Ma, Yubin; Zhou, Minyu; Liang, Jinying; Yang, Jun; Lv, Zhiyue (Frontiers in Cellular and Infection Microbiology, 2020)
Triatoma rubrofasciata (T. rubrofasciata), one kind of triatomine insects, is the vector of Trypanosoma cruzi (T. cruzi), which lead to American trypanosomiasis. Although the gut microbiome may play an essential role in the development and susceptibility of triatomine, there is limited research on the gut microbiota of T. rubrofasciata. To elucidate the effect of the vector’s developmental stages and environmental conditions on the gut microbiome, we employed 16S rRNA gene sequencing to profile the gut bacterial community diversity and composition of T. rubrofasciata. Significant shifts were observed in the overall gut microbe diversity and composition across the development of T. rubrofasciata and specific bacteria were detected in different stages. Serratia and Burkholderia-Caballeronia-Paraburkholderia were dominant in the 1st nymphal stage, while the abundance of Staphylococcus was low in the 1st nymphal stage. Oceanicaulis were undetectable in the adult stage and Odoribacter peaked in the 2nd nymphal stage. Moreover, Staphylococcus was correlated negatively with Serratia. Likewise, the total gut microbiota diversity and composition of T. rubrofasciata differentiated significantly by environmental conditions. The ingestion of a bloodmeal increased alpha diversity of gut bacterial communities, and Staphylococcus was more abundant in laboratory-reared bugs whereas Enterococcus enriched in wild-caught bugs. Furthermore, Pantoea was negatively correlated with Staphylococcus, and positively related to Bacillus only. The phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) algorithm showed obvious metagenomic functional differences by environmental conditions, and Chagas disease relevant pathway was enriched in wild-caught T. rubrofasciata.